Development and distribution of submarine channels associated with sediment gravity flows in the modern Huanghe (Yellow River) subaqueous delta - An, Shikang; Feng, Aiping; Feng, Wei; Wang, Ya Ping; Chen, Yufeng; Wu, Zhuoyi; Chen, Xiaolong; Yu, Yonggui; Pan, Yupeng; Liu, Shihao (Frontiers in Marine Science, 2024)
Gravity-driven depositional processes play a pivotal role in shaping the geomorphology of subaqueous deltas worldwide, particularly by eroding the seafloor, leading to the formation of rugged submarine channels (SCs) and triggering various subaqueous geohazards. A comprehensive understanding of SCs is crucial for elucidating these depositional mechanisms and mitigating the risks associated with submarine geohazards. Although SCs in the Huanghe delta front have been previously identified, often described as seafloor gullies or subsurface "disturbed strata," most studies have primarily concentrated on their engineering geological properties. However, there has been limited research on the scale, morphology, and development of these SCs, especially those that are buried within the stratigraphy. This study integrates highresolution sub-bottom data, sediment core analyses, and historical bathymetric data to investigate the morphology, distribution, and formation mechanisms of SCs in the Huanghe subaqueous delta. The SCs, both buried and exposed, are widespread along the middle and upper delta front, predominantly located at or near the landward flank of sediment gravity flow (SGF) -related accumulations.The buried SCs are characterized by cut-and-fill structures with transparent to semi-transparent fills, indicating rapid infilling processes as SGF energy dissipates. These buried channels were preserved within different sets of delta